Factors affecting the income of Cassiavera farmers in Kerinci Regency - Nurhayani, Nurhayani; Haryadi, Haryadi; Zulfanetti, Zulfanetti (Anjoro: International Journal of Agriculture and Business, 2022)
Cassiavera's contribution to the regional economy of Kerinci Regency is 5.58%, 6.35% to the gross value added, and 21.23% the contribution to regional exports. Cassiavera's lands are mostly controlled by "white-collar farmers" or in The local language is called ”land lord”. If there is an increase in the price of Cassiavera, then the "white-collar farmers" will benefit, not the cultivators or "black-collar farmers". “Black-collar farmers” are those who actually work on Cassiavera lands, only labor or wage farmers with a piece-work or daily system. The increase in Cassiavera prices does not directly increase the welfare of Cassiavera farmers. This study aims to analyze and determine the factors that affect the income of Cassiavera farmers in Kerinci Regency. The analytical method used is descriptive Crosstab method and multiple linear regression with Ordinary Least Square (OLS). The results of the Crosstab tabulation show that there is a relationship between Cassiavera's age, education, labor and land area with Cassivaera's farm income, while the number of stems has no relationship with Cassivaera's farm income. The results of this regression indicate that, partially Cassiavera age, labor and land area have a significant and significant effect on the income of Cassiavera farmers in Kerinci Regency, while the number of stems and education have no effect on the income of Cassiavera farmers. Simultaneously, all variables of Cassiavera age, number of stems, education, labor and land area have a significant effect on farmers' income.